Detection of lead, mercury and arsenic in three natural spring water in Negeri Sembilan / Mohamad Shahrimi Hashim and Faikah Awang @ Ismail - Hashim, Mohamad Shahrimi; Awang @ Ismail, Faikah (Universiti Teknologi MARA, Negeri Sembilan, 2016)
This study focus on detection of lead (Pb), mercury (Hg) and arsenic (As) in three selected natural spring water (NSW) in Negeri Sembilan. Three selected NSW are from Bukit Miku, Kaki Gunung Angsi and Bukit Tangga which located at difference district around Negeri Sembilan. The sampling was done in August 2016 using High Density Polyethylene (HDPE) bottles which are labelled correctly. All sample was analysis using spectrometer while following APHA-3125 method. The statistical analysis was conducted using analysis of variance (ANOVA). The concentration of Pb in NSW collected from Kaki Gunung Angsi has recorded the highest significant amount (0.27367 ± 0.025325 µg/L). On the other hand, NSW taken from Bukit Tangga (0.02533 ± 0.010786 µg/L) andBukit Miku (0.02500 ± 0.004583 µg/L) showed no significant difference (p < 0.05). For Hg, only one NSW which was obtained from Bukit Miku (0.16167 ± 0.011015 µg/L) produced a recordable result. Meanwhile, NSW from Bukit Tangga and Kaki Gunung Angsi did not showed any detectable Hg element in their samples. As content in NSW taken from Bukit Miku, Bukit Tangga and Kaki Gunung Angsi is 0.58700 ± 0.023000 µg/L, 0.20500 ± 0.061612 µg/L and 0.08300 ± 0.003464µg/L respectively. There is significant difference (p < 0.05) in As content between NSW that was obtained from all three locations.